Direct identification of an endogenous peptide recognized by multiple HLA-A2.1-specific cytotoxic T cells. - Henderson, R A (1993)
An endogenous peptide recognized by a murine T-cell clone specific for the human class I major histocompatibility complex-encoded molecule HLA-A2.1 was identified through the use of microcapillary high-performance liquid chromatography coupled with electrospray-ionization tandem mass spectrometry. The peptide was associated with HLA-A2.1 on both normal cells and the antigen-processing-mutant cell line T2. This observation demonstrates that a processing mechanism other than that involving the transporter associated with antigen processing (TAP) proteins 1 and 2 can produce peptides that can be recognized by T cells. The peptide was also recognized by four other independently derived murine HLA-A2.1-specific murine T-cell clones. This suggests that xenogeneic responses are directed at a restricted subset of major histocompatibility complex product-associated peptides. Finally, quantitation of this peptide in cell extracts using mass spectrometry showed it to be among the most dominant HLA-A2.1 associated species on human lymphoid cells. The potential relevance of this observation to models of alloreactivity will be discussed. The methodology described should be generally useful for the identification of peptide epitopes recognized by alloreactive, tumor-specific, and autoimmune T cells.